The effects of outdated data and outliers on Zambia’s 2019 Global Food Security Index score and ranking - Hendriks, Sheryl L. (University of Pretoria, 2021)
Mini-Dissertation (MSc Agric (Agricultural Economics))--University of Pretoria, 2021.